Chromosome Studies in Hypoptopomatinae (Pisces, Siluriformes, Loricariidae): L. XX/XY Sex Chromosome Heteromorphism in Pseudotocinclus tietensis - Andreata, Artur Antonio; De Almeida-Toledo, Lurdes Foresti; De Almeida, Silvio; Filho, Toledo; Oliveira, Claudio (International Society of Cytology, 1992)
The cytogenetic analysis of 13 specimens (9 males and 4 females) of Pseudotocinclus tietensis showed that this species has 2n=54 chromosomes (26M+20SM+6ST) plus one heteromorphic pair (SM/M) in the males and one homomorphic pair (SM/SM) in the females. Ag-NORs are located interstitially on the long arm of the largest metacentric pair and a small amount of constitutive heterochromatin is present in the karyotypes. The occurrence of a heteromorphic pair in the males is demonstrable by the presence of one extra C-banded block in the Y chromosome. The presence of one heterochromatin block distinguishing the sexual chromosomes suggests that this species presents a very primitive mechanism of sex chromosome differentiation. © 1992, Japan Mendel Society, International Society of Cytology. All rights reserved.
Keywords: C-band; Karyotype; NOR; Pseudotocinclus; XX/XY sex chromosomes